PEREMPUAN DI PERSIMPANGAN PEREMPUAN DALAM WACANA MEDIA: MELIHAT GENDER DISCOURSE PADA NOVEL â€œSAMIRA DAN SAMIRâ€ KARYA SIBA SHAKI - Muna Madrah (Program Studi Ilmu Komunikasi FBIK Unissula, 2011)
Open Journal SystemsJournal HelpUserUsernamePassword Remember meÂ NotificationsViewSubscribe / UnsubscribeJournal Content SearchÂ Â BrowseBy IssueBy AuthorBy TitleOther JournalsFont SizeMake font size smaller Make font size default Make font size largerInformationFor ReadersFor AuthorsFor LibrariansPortalHomeAboutLog InRegisterSearchCurrentArchivesHome > Vol 2, No 1 (2011) > MadrahÂ PEREMPUAN DI PERSIMPANGAN PEREMPUAN DALAM WACANA MEDIA: MELIHAT GENDER DISCOURSE PADA NOVEL â€œSAMIRA DAN SAMIRâ€ KARYA SIBA SHAKIOleh Muna Madrah Muna MadrahAbstractSamira and Samir novel written by Siba Shakib an Iranian woman who grew up in Germany. Translated into Indonesian by Lilly Tauhida and published by Alvabet Bandung. This novel contains the discourses of gender debate so that it becomes attractive to the surgeon more than just enjoyed only as a literary work. This novel tries to present how the community construct â€œmaleâ€ and â€œwomanâ€ and what happens if a person was born a woman isÂ Â constructed as male.